Body composition and sexual hormones for the glucose control of autoimmune diabetes in males: are they necessary to predict diabetes-related complications? - García Ramírez, Mireia; Rebollo Román, Ángel; Palomares Ortega, Rafael; Alonso-Echague, Rosario; Calle-Castro, María Luisa; Gálvez Moreno, María Ángeles; Molina Puerta, María José; Herrera-Martínez, Aura D. (Frontiers in Endocrinology, 2023)
Background: Glucose control in diabetes is essential for avoiding diabetes-related complications.Aim: To determine the impact of body composition and sexual hormones in glucose control and diabetes-related complications, in males with autoimmune diabetes.Patients and methods: Thirty-nine patients with autoimmune diabetes and flash glucose monitoring were included. A morphofunctional nutritional evaluation with bioelectrical impedance vector analysis (BIVA), abdominal adipose tissue ultrasound, rectus femoris ultrasound and biochemical parameters, was performed Results: Strong, positive correlations were observed between body composition parameters, biochemical variables and sexual hormones (p<0.05). Adipose tissue measured by BIVA and ultrasound was more significantly associated with glucose control (including time in range >70%, glucose variability <36% determined by flash glucose monitoring; p<0.05) and the presence of microvascular/macrovascular complications (p<0.05) than lean mass. After adjusting by the duration of diabetes, BMI, abdominal circumference, fat mass and phase angle increased the risk for microvascular complications (OR 1.